Pericyclic Reactions for Antivirals: Synthesis of 4-Bromo-N-[(1R*,4S*)-4- hydroxy-2-cyclohexen-1-yl]-2-thiazolecarboxamide - Al-Saad, Dalya; Memeo, Misal G.; Quadrelli, Paolo (Letters in Organic Chemistry, 2016)
Background: Nitrosocarbonyl intermediates are fleeting compounds obtainable from the periodate oxidation of hydroxamic acids and easily trapped with dienes and alkenes to give the products of hetero Diels-Alder and ene reactions in high yields. Methods: A fleeting heterocyclic nitrosocarbonyl derived from the corresponding nitrile oxide is at work in a short-cut synthesis of 4-bromo-N-[(1R*,4S*)-4-hydroxy-2-cyclohexen-1-yl]-2-thiazolecarboxamide. The synthetic strategy is based on hetero Diels-Alder cycloaddition followed by mild reductive cleavage of the N-O bond. Results: A new 2-thiazolecarboxamide derivative is obtained in good yields and the results of the invitro antiviral tests are briefly discussed. The product was found active against HPV virus and some structural evidences allow shining some light on future perspectives on the application of pericyclic reactions to the synthesis of biological active molecules. Conclusion: The findings demonstrated that the synthetic methodology works well for the preparation of heterocyclic substituted novel compounds that displayed interesting and promising activity against viruses and in particular against the HPV.
Keywords: thiazole derivatives